Pengaruh Nasabah Experience dan Fitur Layanan pada BRI Mobile Banking (BRImo) terhadap Kepuasan Nasabah PT. BANK RAKYAT INDONESIA (PERSERO) TBK KC Rajawali Surabaya - Cahyati, Hana Ayuning; Pujianto, MM, Drs. Agung; Mulyati, MM, Dra. Diana Juni (Research Journal of Social Science and Economics, 2025)
Abstract The growth of technology and information is currently growing rapidly and penetrated into all aspects of people’s lives. The main driver is moving towards digitalization. Advances in banking technology today have made a move towards digital banking. Along with the developments of BRI, there are so many innovations, one of which is BRI mobile banking. BRImo is the latest version of BRI mobile developed by BRI in terms of security and features. The security system of BRImo itself is better than BRI Mobile. This study aims to analyze and determine the effect of customer experience and service features on customer satisfaction using mobile banking (BRImo). As for the type of research used is quantitative research, data collection by distributing questionnaires, the number of samples in this study were 99 respondents. The data analysis technique used in this study is regression analysis with a non-linear approach, T test, coefficient of determination R2 and F test. The results of this study indicate that partially customer experience and service features have a positive effect on customer satisfaction using Brimo mobile banking with a score for customer experience 0.000 > 0.05 which means significant and for service features the resulting significant value is 0.000 > 0.05. and for the F test in this study it could not be carried out because 2 variables were not linear, namely the Customer Experience variable (X1) and service features (X2) so that the F (simultaneous) hypothesis test could not be proven